Financing public investments in the capitalist economy and its economic and social effects: understanding its importance through history and Keynes’s theory - Cutrim Carvalho, André; Ferreira Carvalho, David; Silva dos Santos, Cleyson; Silva de Oliveira, Luana Isabel; Filgueiras, Gisalda Carvalho (Espacio Abierto, 2024)
The 1930s are historically recognized as the decade of the 1929 Crash and the years of economic non-stagnation for the US government and those of several European countries. The so-called “Keynesian” policies, despite being successful experiences, were continuously “attacked” ever since John Maynard Keynes launched his General Theory (GT). The success of the GT may be attributed to the significant reduction in unemployment at the time, mainly due to an increase in public investment spending. This is because the main device available for public administration to reduce a high unemployment rate, when an economy is in a cyclical state of recession/depression, is public investment, preferably investment in basic social capital. Having made this preamble, the main objective of the article is to discuss the importance of financing public investments in the capitalist economy and its economic and social effects, having as a basis for this the history and the economic theory of John Maynard Keynes. For this, it is crucial to adopt an exploratory, qualitative and bibliographic approach as a methodological procedure. It may be concluded that the only egress to stimulate private investment in times of crises, apart from measures to support consumption through social programs for the unemployed, is government investment. This is because government investments are autonomous investments, i.e., they do not depend on interest, nor on income. Furthermore, autonomous investment decisions, especially in the construction of public works with huge economic (roadways, ports, railways) and social (schools, hospitals and housing) repercussions, tend to break the barrier of distrust in relation to the future and promote a dynamic effect on the economy and society as a whole. Keynes, therefore, emphasizes the importance of governmental intervention to stabilize the economy. The importance of Keynes’s economic theory lies in the fact that his ideas brought a new perspective to economic theory and helped shape the economic policies implemented in many countries to this day. His contributions paved the way for a better understanding of economic dynamics, whether in the public or private sector, in stabilizing the economy, especially in times of crisis, and in promoting social welfare.